2020
DOI: 10.3389/fpsyt.2020.580736
|View full text |Cite
|
Sign up to set email alerts
|

Tele-Psychiatry Assessment of Post-traumatic Stress Symptoms in 100 Patients With Bipolar Disorder During the COVID-19 Pandemic Social-Distancing Measures in Italy

Abstract: The acute phase of the COrona VIrus Disease-19 (COVID-19) emergency determined relevant stressful burdens in psychiatric patients, particularly those with chronic mental disorders such as bipolar disorder (BD), not only for the threat of being infected but also for the strict lock-down and social-distancing measures adopted, the economic uncertainty, and the limited possibilities to access psychiatric services. In this regard, telepsychiatry services represented a new important instrument that clinicians could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 58 publications
2
51
0
Order By: Relevance
“…It may be that clinical samples may be more vulnerable to the adverse mental health effects of COVID-19, as has been found in other disasters ( Zvolensky et al, 2015 ). In fact, individuals receiving outpatient telehealth services during the Stay-At-Home order and those who were diagnosed with psychiatric disorders endorsed elevated levels of posttraumatic stress during Stay-At-Home orders compared to individuals who did not have pre-existing mental health conditions ( Carmassi et al, 2020 ; Hao et al, 2020 ), and these symptoms were especially elevated among women with Bipolar disorder ( Carmassi et al, 2020 ). Third, data were collected via self-reports.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that clinical samples may be more vulnerable to the adverse mental health effects of COVID-19, as has been found in other disasters ( Zvolensky et al, 2015 ). In fact, individuals receiving outpatient telehealth services during the Stay-At-Home order and those who were diagnosed with psychiatric disorders endorsed elevated levels of posttraumatic stress during Stay-At-Home orders compared to individuals who did not have pre-existing mental health conditions ( Carmassi et al, 2020 ; Hao et al, 2020 ), and these symptoms were especially elevated among women with Bipolar disorder ( Carmassi et al, 2020 ). Third, data were collected via self-reports.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, specific attention should be paid to this vulnerable population. Indeed, recent research has found that patients with psychiatric problems had high levels of mental health burden (including PTSD and insomnia) when they were exposed to lockdowns and spatial distancing (Carmassi, Bertelloni, et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although patients have recovered from the infection and finished quarantine for medical observation, they are suffering from social isolation and economic problems or unemployment because of the diagnosis (37). Consistently, a recent study also reported that COVID-19-related financial and social difficulties or concerns were a major risk factor for psychological distress in subjects (38). Therefore, disturbing social problems may be more strongly linked to psychological distress in patients.…”
Section: Discussionmentioning
confidence: 87%